COMPARATIVE CHARACTERISTICS OF TRIGLYCERIDE CONTENT IN FEMALE RATS’ PERIODONTAL TISSUES UNDER IMBALANCED RATION - H.V. Pogrebnyak (Український стоматологічний альманах)
This paper presents the survey findings concerning the primary indices of lipid metabolism, i.e. triglycerides in the periodontal tissues of female rats, which were kept on imbalanced rations.